Analysis of the concepts of legal regulation of Smart contract - Bazarov, M.M.; Tokatov, R.A. (Bulletin of the Karaganda University “Law Series”, 2024)
The purpose of the study is to study smart contracts, which are one of its main components, which support the main connection between the parties forming social relations, using the innovative technology — blockchain technology. It is focused on the analysis of the formation of smart contracts and the peculiarities of legal regulation in domestic and international relations. To form smart contracts, its general concept and specific features, the potential of blockchain technology in forming smart contracts are studied. Priorities and weaknesses of the technological system in the formation of smart contracts are revealed. Foreign experiences have been studied, and the basis of the legislation of Kazakhstan, including civil law legislation, has been studied for the implementation of smart contract formation technology mechanisms. The advantages and disadvantages of smart contracts, which play an important role in the implementation of blockchain technology, are discussed, and the situations that allow them to be prevented are explained. As a result of the research, the legal basis for the introduction of this information and communication technology into the Kazakh legislation was determined. Conclusions about smart contracts, which rapidly develop blockchain technology, are important as scientific research opens the way for legal research in this direction, considering contractual relations in social relations as a tool for improving them. The practical significance of the research will be to increase the efficiency of the measures taken in the formation of smart contracts, to contribute to the development of electronic contractual relations that allow the formation of public relations at a high-quality legal level, and as a result, to create the basis for social and economic development. Research results can be used in the formation of smart contracts, public and quasi-public procurement, public service provision, and many other areas.